ANALISIS FAKTOR-FAKTOR PENYEBAB KESULITAN BELAJAR PKn PADA SISWA KELAS XI IPA DI SMA PLUS BINA BANGSA PEKANBARU - Nani Nurhidayah; Gimin Gimin; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: the background of the number of students' student learning activities, both internal and external factors. The title of the study "Analysis of factors causing learning difficulties Civics in students of class XI IPA in SMA Plus Bina Bangsa Pekanbaru". Formulation of the problem "What are the factors causing the difficulties of learning Civics in the students of grade XI IPA in SMA Plus Bina Bangsa Pekanbaru?" The purpose of the study "Knowing factors causing learning difficulties Civics in students of class XI IPA in SMA Plus Bina Bangsa Pekanbaru". The study population is 18 students of grade XI IPA in SMA Plus Bina Bangsa. Data analysis using Qualitative Descriptive analysis. The results of this study indicate that factors causing the difficulty of learning Civics in students of class XI IPA in SMA Plus Bina Bangsa Pekanbaru are internal factors of 79% very high category, the sub indicators are cognitive (intelligence) 81% very high category, sub indicators affective attitude 85% very high category, interest 90% category is very high, motivation 78% category is very high, and sub indicators are psychomotor physical condition 75% high category and state of senses 56% very high. External factors 89% very high category, sub-indicator family environment family social economy 92% category very high, education parent 90% category very high, attention of parents and atmosphere among family member 90% very high category. sub indicators of school environment facilities and infrastructure 94% very high category, teacher and student competence 94% very high category and learning method and learning materials 92% very high category. In sub indicators of socio-cultural environment 82% very high category, participation of education 78% very high category.Keywords: Factors Causing Learning Difficulties